Forest of Pt–Au–Ag tri-metallic nanodendrites as an efficient electrocatalyst for methanol oxidation reaction. Issue 9 (24th December 2014) - Huan, Tran Ngoc; Shinde, Dipak V.; Kim, Saetbyeol; Han, Sung-Hwan; Artero, Vincent; Chung, Hoeil
Abstract : Forests of trimetallic nanodendrites composed of Pt, Au, and Ag have been synthesized and their catalytic performances with regard to the methanol oxidation reaction (MOR) were evaluated. Abstract : Forests of trimetallic nanodendrites composed of Pt, Au, and Ag have been synthesized and their catalytic performances with regard to the methanol oxidation reaction (MOR) were evaluated. Analysis based on elemental mapping revealed homogeneous incorporation of Pt, Au, and Ag throughout the nanodendrite and single crystalline structure. These materials proved active for MOR, with improved electrocatalytic performances with regards to Pt in terms of both overpotential and stability.